The Use of LigaSure™ Does not Affect Histologic Margin Assessment in Pancreatoduodenectomy (PD) Specimens - Del Chiaro, Marco; Blomberg, John; Segersvärd, Ralf; Rangelova, Elena; Ansorge, Christoph; Verbeke, Caroline (JOP. Journal of the Pancreas, 2014)
Context LigaSureTM is considered safe in performing pancreaticoduodenectomy (PD). However, no data are available regarding the possible damage of tissues at the resection margins and the impact thereof on histologic margin assessment. Objective This study compares the degree of histologic damage to the resection margins when using LigaSureTM (Group 1) or traditional ligature (Group 2). Methods Both groups included 8 consecutive patients who underwent PD at Karolinska Institute in December 2013 (Group 1) or earlier (Group 2) by the same surgeon (M.D.C.). The quality of tissues at the circumferential margins was compared between both groups by scoring for three different kinds of damage: tissue fragmentation, hemorrhage, and cell damage. Results The mean score for fragmentation was 1.3 (Group 1) versus 1.7 (Group 2; P=0.1). For hemorrhage the mean score was 0.8 (Group 1) versus 1.5 (Group 2; P=0.04). The mean score for cell damage was 1.4 (Group 1) compared to 1.2 (Group 2; P=0.1). Conclusions LigaSureTM does not cause tissue damage that could affect histologic margin assessment in PD specimens. Image: Tissues at the resection margin.